GEOGRAPHICAL ANALYSIS OF THE FLOODING SITUATION NEAR ATYRAU DURING THE SPRING FLOOD (Journal of Geography and Environmental Management, 2025)
In the spring of 2024, Kazakhstan faced a catastrophic flood that covered the northern, western and eastern regions of the country and caused significant economic damage. During the flood, the city of Atyrau and its surroundings were threatened with flooding. Purpose of the study - аnalyzing the water regime of the Zhaiyk River, to identify and show the dynamics of the factors that contributed to the flood, as well as the features of the spatial distribution of floods. In the analysis of the flooding process, data from hydrological posts were used. Work was carried out on decoding Sentinel 2A satellite images in ArcGIS Pro 3.2 to demonstrate the spatial distribution of water and maps were compiled. This article provides a geographical analysis of the process of flooding the city of Atyrau and the surrounding territories during the spring 2024 flood. The spatial distribution of flooding, climatic conditions affecting it, terrain and anthropogenic factors are considered in detail. The results of the study will help to understand the nature of flooding, develop strategies to reduce its damage and effectively manage water resources. However, the fight against such natural disasters requires an integrated approach that combines scientific research and active interaction with local executive bodies.
Keywords: suburb of the Atyrau city; Zhaiyk River; spring flood; geographical analysis; factors shaping floods